BEAHIAN: THE ECONOMIC TRADITION OF MUTUAL COOPERATION IN THE KUANG DALAM MALAY COMMUNITY - Aravik, Havis; Hamzani, Achmad Irwan; Khasanah, Nur (Ekonomica Sharia: Jurnal Pemikiran dan Pengembangan Ekonomi Syariah, 2025)
The beahian tradition—reciprocal labor exchange in the Malay Kuang Dalam community—faces significant challenges due to modernization and shifting social values, leading to the decline of communal work practices and the rise of wage-based labor. This study aims to document, analyze, and evaluate beahian as both an intangible cultural heritage and a model of economic cooperation grounded in Islamic principles and social capital, while identifying its potential for revitalization to strengthen rural economic resilience. Employing a qualitative approach with ethnographic methods, data were collected through in-depth interviews, participant observation, and documentary studies in Kuang Dalam Village, Ogan Ilir. Data analysis followed a descriptive-qualitative framework using Miles et al.’s interactive model, with source and method triangulation to ensure validity. Findings reveal that beahian functions not only as an efficient and low-cost labor distribution mechanism but also as a means of reinforcing social cohesion through the values of ukhuwah (brotherhood), ‘adalah (justice), and ta’awun (mutual assistance). From an Islamic economic perspective, beahian resembles a mudharabah contract based on labor exchange, while in social capital theory, it represents strong bonding social capital built on trust, reciprocity norms, and dense social networks. The study concludes that beahian holds strategic relevance for adaptation as a sustainable and equitable local economic collaboration model in the era of globalization.